Vitamin D Serum Level in Patients with Schizophrenia in West Java, Indonesia - Nofan Pratama Maulana; Tuti Kurnianingsih; Sumartini Dewi (Althea Medical Journal, 2020)
Background: Vitamin D is an immune-regulator that influences the neuro-inflammation process in schizophrenia. The study aimed to explore the vitamin D serum level in schizophrenic patients at the outpatient clinic of the Provincial Mental Hospital, West Java, Indonesia.Methods: A quantitative descriptive study was conducted in November-December 2019 using secondary data of all-male schizophrenic patients at the Provincial Mental Hospital. Data collected were demographic characteristics, clinical characteristics, and vitamin D Level. Scoring was then performed using Positive and Negative Syndrome Scale (PANSS) and Montreal Cognitive Assessment (MoCA) to assess the positive and negative symptoms as well as the cognitive symptoms based on the serum vitamin D levels.Result: All male schizophrenic patients had a low serum vitamin D level (mean16.67±5.6ng/ml) with 64.52% of them had vitamin D deficiency (<20 ng/ml). Interestingly, patients with vitamin D deficiency had a negative symptom (mean22.1±5.6ng/ml) whereas those with vitamin D insufficiency (20-29 ng/ml) had a positive symptom (mean 18.55±5.6ng/ml). Furthermore, patients with vitamin D deficiency had a lower impaired cognitive function value (mean 19.7±3.4ng/ml) compared to those with vitamin D insufficiency.Conclusions: A low vitamin D serum level in schizophrenic patients may play a role in the pathogenesis of this disorder. Further studies are needed to confirm this finding.